1992
DOI: 10.1093/brain/115.5.1563
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Appraisal of Neuropsychological Correlates of Japanese Ideogram (Kanji) and Phonogram (Kana) Reading

Abstract: Owing to the Japanese language's unique writing system, which consists of phonograms and ideograms, reading impairments of Japanese brain-damaged patients have attracted the interest of many researchers. Past case reports as well as some widely accepted handbooks and textbooks have concluded that a specific aphasia type or lesion site is associated with a particular impairment pattern of phonograms and ideograms in reading. However, the methodology and analytical procedures in previous studies were inadequate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…It has been criticized that previous reports correlating particular impairment patterns to the brain lesion of the patient seemed oversimplified [17]. Sugishita et al [17 ]argued that impairment of high cortical functions such as reading phonogram or ideogram might not be directly linked to the damaged structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been criticized that previous reports correlating particular impairment patterns to the brain lesion of the patient seemed oversimplified [17]. Sugishita et al [17 ]argued that impairment of high cortical functions such as reading phonogram or ideogram might not be directly linked to the damaged structure.…”
Section: Discussionmentioning
confidence: 99%
“…Sugishita et al [17 ]argued that impairment of high cortical functions such as reading phonogram or ideogram might not be directly linked to the damaged structure. The authors postulated that complex cognitive functions accomplished through many interfaces on various stages of mental process related to the neural network, and that it may be too risky to match the cognitive dysfunction directly with the damaged area of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Also, several lines of studies have suggested the contribution of the right hemisphere in the visual recognition of logograms (Yamaguchi, Toyoda, Xu, Kobayashi, & Henik, 2002;Kamada et al, 1998;Nakagawa, 1994;Sugishita, Yoshioka, & Kawamura, 1986;Hatta, 1977;Sasanuma, Itoh, Mori, & Kobayashi, 1977). Nonetheless, the issue seems not fully resolved, as for instance, a more recent multiple case study found no consistent correlation between specific patterns of impairment and lesion sites (Sugishita, Otomo, Kabe, & Yunoki, 1992). In the brain imaging literature, moreover, although a few previous studies have examined brain activity during reading of Japanese (Sakurai, Momose, Iwata, Sudo, et al, 2000;Sakurai, Momose, Iwata, Ishikawa, et al, 1996; Sakurai, Momose, Iwata, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of phonogram and ideogram originated from Japanese in which dual orthographic system is employed; Kana (phonograms) and Kanji (ideograms) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Japanese authors have found a double dissociation between Kana and Kanji impairments in brain-damaged patients and reported that Kanji is processed mainly in left posterior inferior temporal area (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Japanese authors have found a double dissociation between Kana and Kanji impairments in brain-damaged patients and reported that Kanji is processed mainly in left posterior inferior temporal area (4)(5)(6)(7)(8)(9). On the contrary, there have been few studies on Korean written language (13,14), another orthographic system that also uses both phonogram (Hangul) and Chinese ideogram (Hanja).…”
Section: Introductionmentioning
confidence: 99%